Rain, rain, smurf away - Peyo (Simon Spotlight, 2012)
After days of endless rain, Handy Smurf decides to smurf a weather machine to make it go away, but what happens when Farmer Smurf and Poet Smurf get their hands on the machine and can't decide if it should be a sunny or rainy day?